Management model for productivity improvement in the craft beer production process through the application of demand planning techniques, EOQ and MRP - Negron Aching, Jimena (2025)
The craft beer industry has developed in the Peruvian market by 2023, representing sales of 2.33 billion; However, its productivity rate of 12% is still low compared to the industry's average productivity of 55%. Among the causes of the problem, the lack of a production plan and a demand forecasting system was identified; Therefore, the objective of this study is to develop a forecast model for the demand for beer and the economic order quantity of raw materials to develop an adequate production and supply plan to increase productivity in the study company. The Winters demand forecast model was selected by analyzing the mean absolute percentage forecast error (MAPE) indicator of 9.4%, assuming +/- 10% MAPE as a limit and the similarity of the model's behavior with respect to the historical demand of the company. The proposed model was validated through simulations using software in Excel and @Risk. The research has shown a 48% increase in productivity compared to the initial value, achieving an increase of 3’905,656 PEN in the income of the craft beer company investigated.